Development and survival of cattle gastrintestinal nematode larvae, during the dry season, in the Pantanal Mato-Grossense region, Brazil - Catto, João Batista (Pesquisa Agropecuaria Brasileira, 2014)
Survival and migration of infective larvae of cattle parasite gastrintestinal nematodes observed on a pangola grass (Digitaria decumbens) pasture exclosure, where dung pats were monthly placed. At 25 to 35 days intervals the dung pat and the surrounding vegetation were analysed for presence and quantity of infective larvae. It was concluded that, in the studied region, the dung pat offers survival conditions to free living forms during the dry season. Infective larvae migration increased with rainfall, proportionally to intensity and frequency of rains. From the total of pasture recovered larvae, 66% belonged to the genus Cooperia, 17,3% to Haemonchus and 16,5% were identified as Oesophagostomum sp. larvae of Trichostrongylus occurred in inexpressive numbers.